2011
DOI: 10.1102/1470-5206.2011.0002
|View full text |Cite
|
Sign up to set email alerts
|

Adult-onset cystic hygroma: a case report and review of management

Abstract: Cases of cystic hygroma are rare and this report highlights the need for further research into treatment options. A 24-year-old Lithuanian woman was referred for further investigation of a painless but restricting right-sided neck swelling. This case report discusses the differential diagnosis and up-to-date management of cystic hygroma in the adult.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 18 publications
0
43
0
Order By: Relevance
“…CH usually affects children under 2 years of age (80–90%) with incidence of 1.2 to 2.8 per 100,000 infants [10, 11]. CH does not show any gender preference; both genders are equally affected [12, 13].…”
Section: Introductionmentioning
confidence: 99%
“…CH usually affects children under 2 years of age (80–90%) with incidence of 1.2 to 2.8 per 100,000 infants [10, 11]. CH does not show any gender preference; both genders are equally affected [12, 13].…”
Section: Introductionmentioning
confidence: 99%
“… 1–3 Case reports of cystic hygroma in the adult are exceedingly rare and a recent report has estimated that fewer than 150 cases can be found in English-language scientific literature. 1 Also referred to as a lymphangiomas or lymphatic malformations, 1–3 cystic hygromas are most often found in the cervicofacial region (75%) and are less frequently seen in the axilla (20%) or elsewhere. 4 Previous reports have discussed the management of cystic hygromas in the adult, but these reviews are limited to presentations in the neck.…”
Section: Introductionmentioning
confidence: 99%
“…Ho et al reported a case of an adult-onset cystic hygroma in a 34 year old female from foreign body reaction to a retained wood in the neck following an episode of domestic violence [2]. However, etiology of most acquired cystic hygroma is uncertain even in documented cases of rapid development of symptoms [3,4]. The usual slowly progressive growth of this lesion coupled with absence of pressure symptoms on the aero-digestive tract and restriction of neck movements in adults may explain the reason for her late presentation to our clinic.…”
Section: Discussionmentioning
confidence: 99%